Heat-transfer-enhanced high-stability noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst as well as preparation method and application thereof

By using multi-layer core-shell structure and high thermal conductivity materials in the dehydrogenation catalyst, the problems of heat aggregation and water vapor poisoning during catalytic combustion are solved, the stability and heat transfer efficiency of the catalyst are improved, and the life of the catalyst is extended.

CN119303607APending Publication Date: 2025-01-14SOUTHWEST RES & DESIGN INST OF CHEM IND

Patent Information

Application Number
CN202411325691.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing dehydrogenation catalysts have problems such as heat accumulation and water vapor during catalytic combustion, which reduces the stability and life of the catalyst.

Method used

A multi-layer core-shell structure consisting of an alumina support, a defect anchoring layer and a precious metal layer is adopted, combining high thermal conductivity materials and protective shells to enhance heat transfer efficiency and inhibit the toxicity of water vapor to the catalyst.

Benefits of technology

It improves the heat transfer uniformity and low-temperature activity of the catalyst, extends the service life of the catalyst, and reduces the replacement cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a heat transfer enhanced high-stability noble metal catalytic oxidation dehydrogenation multilayer core-shell catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysts. The catalyst sequentially comprises an aluminum oxide carrier inner core, a defect anchoring layer, a noble metal layer and a protective shell layer from inside to outside, wherein the alumina carrier is particles prepared by mixing active gamma-Al2O3 and a coated high-heat-conductivity-coefficient material, and the defect anchoring layer is composed of oxides having strong interaction with metal; the precious metal layer is composed of precious metal element Pd, and the protective shell layer is made of porous SiO2. The invention also discloses a preparation method of the catalyst and application of the catalyst in dehydrogenation of mixed gas. According to the invention, low-temperature high-efficiency activation of hydrogen can be realized, the dehydrogenation precision of the dehydrogenation catalyst under an industrial operation condition is improved, poisoning and sintering inactivation of H2O to active sites of the dehydrogenation catalyst are inhibited, and the hydrothermal stability is improved. The catalyst is longer in service life and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and specifically provides a heat transfer enhanced highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst, a preparation method and application thereof. Background Art

[0002] CO2 is one of the raw materials for the stripping process of urea production, and comes from the desorbed gas in the shift gas decarbonization section or the low-temperature methanol washing section. The desorbed gas inevitably contains combustible gases such as H2 (less than 1.5%), CO, methanol, and methane, and does not participate in the reaction during the urea synthesis process, resulting in an increase in the concentration of combustible gases in the synthetic ammonia tail gas after condensation and washing. At the same time, in order to prevent corrosion of the synthetic urea device, O2 needs to be added to the raw material CO2 to form a passivation film on the surface of the stainless steel material. The remaining O2 in the synthetic urea tail gas is typically composed of 0.06% CO2, 0.5% NH3, 26.15% H2, 1.12% H2O, 14.34% O2, and 57.9% N2 after mixing with the combustible gas, which is within the explosion limit range and has a great explosion hazard. Therefore, a dehydrogenation device is set in front of the urea synthesis reactor to reduce the H2 concentration in the CO2 gas to 50ppm or even lower through catalytic combustion. Catalytic combustion technology is also used in mixed gases containing less than 1.5% H2 and sufficient O2 in similar chemical production processes. In addition, H2 catalyst combustion is a highly exothermic process. If the heat generated cannot be removed in time, it will destroy the microscopic chemical structure of the dehydrogenation catalyst and reduce the stability of the catalyst. Therefore, a dehydrogenation catalyst with good heat transfer performance, high activity at low temperature, and high stability is the key in catalytic combustion dehydrogenation technology.

[0003] CN1035256A, CN1334140A, CN101543776B, CN113908831A, and CN116099545A disclose the important role of Pd as a catalyst active component in catalytic combustion dehydrogenation reactions. CN116099545A discloses a dehydrogenation catalyst, which uses α-Al2O3 balls as carriers, Pd and Pd as active components, adds Cu or Mo as an additive, and adds at least one of rare earth elements such as Y, Gd or Dy, and is suitable for dehydrogenation of carbon dioxide feed gas at 95 to 100°C. However, H2O produced by the reaction of H2 and O2 will lead to the accumulation of hydroxyl groups on the catalyst surface, promoting the conversion of Pd into Pd-OH to poison active sites. At the same time, Pd-OH is more likely to migrate and sinter, resulting in reduced dehydrogenation activity and shortening the catalyst life.

[0004] CN113908831A discloses a hydrophobic catalyst for negative low-temperature catalytic combustion of hydrogen, with Al2O3 as carrier, the active component noble metal is at least one of Pd, Pt, Rh or Ru, the active component non-noble metal is at least one of Co, Mn, In, Ni, Cu, Ce, Pr, Zr or La, and the catalyst is modified by multi-carbon chain fluorosilane to enhance the hydrophobicity of the catalyst below 30°C, thereby improving the activity and stability of the catalyst. CN116422363A discloses the preparation of a hydrophobic Pd-based catalyst, in which an organic solution containing a silanization agent is subjected to a silanization reaction with the surface of a molecular sieve-supported PdO catalyst in the form of gas bubbling deposition to form a SiO2 shell layer, thereby improving the activity of catalyzing methane combustion under water vapor conditions. However, the temperature of the silanization reaction is relatively high, at 350°C to 500°C.

[0005] The dehydrogenation catalyst disclosed in the above patents does not involve how the mixed gas catalytic combustion dehydrogenation catalyst can enhance the heat transfer efficiency of the catalyst, reduce heat accumulation, and at the same time, promote the desorption of the product H2O, inhibit the poisoning and sintering deactivation of the active sites of the dehydrogenation catalyst by H2O, thereby improving the dehydrogenation accuracy of the dehydrogenation catalyst under industrial operating conditions, enhancing stability and extending life, and reducing the cost of catalyst replacement. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing a highly stable precious metal multilayer core-shell catalyst with enhanced heat transfer for catalytic oxidative dehydrogenation of inert feed gas, so as to solve the technical problems of thermal aggregation of existing dehydrogenation catalysts during use of dehydrogenation devices and poisoning and sintering deactivation of active sites of dehydrogenation catalysts by H2O.

[0007] The second object of the present invention is to provide a method for preparing the catalyst.

[0008] The third object of the present invention is to provide application of the catalyst.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] The present invention discloses a heat transfer enhanced and highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst, wherein the catalyst comprises, from the inside to the outside, an alumina carrier core, a defect anchoring layer, a noble metal layer and a protective shell layer;

[0011] The alumina carrier is a particle made by mixing active γ-Al2O3 and a coated high thermal conductivity material, and the mass of the coated high thermal conductivity material is 0.1% to 3% of the mass of γ-Al2O3;

[0012] The defect anchoring layer is composed of oxides that have strong interactions with metals, including WO a 、TiOb 、CeO c ,In2O3 and SnO d At least one of the following, wherein a=2-3, b=1-2, c=1.5-2, d=1-2, and its content is 2.0-10.0% of the mass of the alumina carrier;

[0013] The noble metal layer is composed of the noble metal element Pd, and its content is 0.05-0.15% of the mass of the alumina carrier;

[0014] The protective shell layer is porous SiO2 with a thickness of 5 to 12 nm.

[0015] In some embodiments of the present invention, the specific surface area of ​​the γ-Al2O3 powder is greater than 400 m 2 / g;

[0016] Preferably, the coated high thermal conductivity material is a high thermal conductivity material with a coating agent coated on the surface;

[0017] More preferably, the high thermal conductivity material includes at least one of ultrafine alumina powder, ultrafine zirconium oxide, aluminum nitride, boron nitride, silicon nitride, and silicon carbide;

[0018] More preferably, the coating agent includes at least one of polydopamine, titanate, silane coupling agent and aluminate, and the coating agent functions to effectively connect the multilayer core-shell structure and generate pores to enhance mass and heat transfer after calcination and decomposition;

[0019] More preferably, the mass of the coating agent is 0.1-3% of the mass of the high thermal conductivity material.

[0020] The high thermal conductivity material of the present invention can enhance the internal heat transfer of the spherical catalyst and reduce the negative impact of uneven heat transfer on the catalytic reaction efficiency.

[0021] The preparation method of the heat transfer enhanced high-stability noble metal dehydrogenation multilayer core-shell catalyst disclosed in the present invention comprises the following steps:

[0022] S1. Preparation of alumina carrier core: ball milling a high thermal conductivity material, a coating agent and a liquid grease, and then adding active γ-Al2O3 powder to mix, and then adding a binder solution, rolling ball forming particles, calcining, to obtain a heat transfer enhanced alumina carrier core;

[0023] S2. Preparation of defect anchoring layer: take an oxide precursor salt having a strong interaction with the metal, add water to prepare a solution, add the alumina support prepared in step S1 to the solution, stir evenly, remove the support after the surface bubbles disappear, dry, and calcine to form a support having a defect anchoring layer;

[0024] S3. Preparation of a noble metal layer: Take the carrier having a defective anchoring layer obtained in step S2, impregnate the noble metal precursor solution by ultrasonic spraying, and obtain a dehydrogenation catalyst precursor by drying, calcining, and liquid phase reduction;

[0025] S4. Preparation of protective shell layer: using chemical vapor deposition method to deposit a solution containing silicon source and surfactant on the surface of dehydrogenation catalyst precursor, and forming a porous SiO2 protective shell after drying and pre-decomposition.

[0026] In some embodiments of the present invention, in step S1, the drying time is 2 to 12 hours at 50 to 120°C; the calcination time is 1 to 8 hours at 300 to 550°C;

[0027] The binder solution comprises a hydroxypropyl methylcellulose solution, and the concentration thereof is 1 to 5 wt %; preferably, the concentration thereof is 4 to 5 wt %.

[0028] Preferably, the size of the ball-forming particles is 2 to 4 mm.

[0029] The liquid oil includes oil with a saturated fatty acid content of more than 50%, preferably palm oil or coconut oil, which functions to efficiently and evenly mix the high thermal conductivity material and the coating agent to achieve a homogenizing effect, form a higher dispersion in the carrier, and enhance adhesion during the ball rolling process to improve carrier strength.

[0030] In some embodiments of the present invention, the amount of liquid grease used is 0.2-1.5% of the mass of the high thermal conductivity material, preferably 0.6%.

[0031] In some embodiments of the present invention, in step S2, the oxide precursor salt includes ammonium tungstate [(NH4)6W7O 24 ·6H2O], titanium oxysulfate [TiOSO4·xH2SO4·8H2O], cerium ammonium nitrate [Ce(NO3)3·6H2O], indium nitrate [In(NO3)3] and tin tetrachloride [SnCl4] at least one;

[0032] The concentration of the oxide precursor salt solution is 0.01 to 1 mol / L; preferably, the concentration is 0.01 to 0.03 mol / L.

[0033] In some embodiments of the present invention, in step S3, the carrier with a defective anchoring layer obtained in step S2 is placed in an ultrasonic oscillator for oscillation, and the noble metal precursor solution is atomized and sprayed onto the carrier beads, and then dried, calcined, and liquid-phase reduced after the impregnation is completed;

[0034] Preferably, the noble metal precursor comprises palladium nitrate and / or palladium chloride;

[0035] Preferably, the concentration of the noble metal precursor solution is 5-10 mg Pd / g.

[0036] Preferably, the drying time is 2 to 12 hours at 50 to 120°C; the calcination time is 1 to 8 hours at 300 to 550°C;

[0037] Preferably, the liquid phase reduction conditions are: immersing the dried and calcined carrier in a reducing agent solution, and performing a reduction reaction at room temperature to 90° C. for 1 to 5 hours; the reducing agent includes at least one of ascorbic acid, hydrated hydrazine and sodium borohydride, and the mass concentration of the reducing agent solution is 0.5 to 6%.

[0038] In some embodiments of the present invention, in step S4, the silicon source includes at least one of hexadecyltrimethylsilane, polydimethylsiloxane, hexamethyldisilazane, tetraethyl orthosilicate, and triisopropylsilane, and the amount of the silicon source is such that the mass fraction of SiO2 in the final catalyst is 0.1 to 0.5%;

[0039] The surfactant comprises at least one of coconut oil monoethanolamide polyoxyethylene ether, octadecylamine polyoxyethylene ether and fatty alcohol polyoxypropylene ether, and the amount of the surfactant is 1 to 10% of the mass of the aluminum oxide;

[0040] The solvent is acetone or ethanol;

[0041] The concentration of the silicon source in the solution containing the silicon source and the surfactant is in the range of 5-15 wt %, and the concentration of the surfactant in the solution is in the range of 10-20 wt %.

[0042] In some embodiments of the present invention, in step S4, the contact time between the solution containing the silicon source and the surfactant and the dehydrogenation catalyst precursor is 2 to 10 seconds, the feed temperature is 50 to 90°C, and the deposition temperature is 240 to 340°C.

[0043] The application of the heat transfer enhanced high-stability noble metal dehydrogenation multilayer core-shell catalyst disclosed in the present invention is applied to the dehydrogenation of a mixed gas with a hydrogen content of less than 1.5%v and containing no less than 0.75%v of oxygen.

[0044] In some embodiments of the present invention, during dehydrogenation, the reaction temperature is 120-180°C, the reaction pressure is normal pressure-10 MPa, and the space velocity is 5000-30000 h -1 .

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] The catalyst of the present invention has a multilayer structure of a γ-Al2O3 carrier with a high specific surface area, a defect anchoring layer, a noble metal layer and a protective shell. The defects of the oxide on the defect anchoring layer are used to stabilize the noble metal active components, and a protective shell is encapsulated on the surface of the noble metal layer. The high thermal conductivity material uniformly dispersed in the alumina carrier allows the catalyst to transfer heat uniformly during application, and the reaction effect is better. The multilayer structure ensures that the noble metal is uniformly and stably dispersed, improves the low-temperature activity and dehydrogenation accuracy, and promotes the desorption of the dehydrogenation product H2O, inhibits the poisoning and sintering deactivation of the active sites of the dehydrogenation catalyst by H2O, and improves the service life of the catalyst. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. If the specific conditions are not indicated in the examples, they are carried out according to the conditions recommended by the normal conditions or the manufacturers. If the manufacturers are not indicated in the reagents or instruments used, they are all conventional products that can be obtained by commercial purchase.

[0048] The specific surface area of ​​the γ-Al2O3 powder in the embodiment of the present invention is greater than 400m 2 / g.

[0049] Example 1

[0050] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:

[0051] Step 1: Take 10g of ultrafine alumina powder and put it into a high-energy ball mill, add 0.05g of titanate and 0.06g of palm oil for surface treatment for 2.5h to obtain modified ultrafine alumina powder.

[0052] Take 0.1g modified ultrafine alumina powder and mix it with 50g active γ-Al2O3 powder, add appropriate amount of hydroxypropyl methylcellulose solution, roll into balls to form particles of 2-4mm, dry at 120℃ for 5h, and calcine at 500℃ for 2h to obtain the alumina carrier core with enhanced heat transfer.

[0053] Step 2: Weigh 3.1g of ammonium tungstate and 13.33g of titanyl sulfate, dissolve in 40mL of deionized water, control the solution temperature at 40°C, quickly add 40g of the alumina carrier core beads obtained in step 1, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 105°C for 8h, and calcine at 500°C for 3h to obtain a carrier 1 with a defective anchoring layer.

[0054] Step 3: Weigh 3g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of the carrier 1 with a defective anchoring layer, put it into an ultrasonic oscillator and oscillate it with a power of 200W; atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads. After impregnation, dry them at 120℃ for 6h and calcine them at 400℃ for 2h. Immerse the beads in a 3.5wt.% hydrated hydrazine solution, reduce them at 40℃ for 3h, then take out the beads and dry them at 120℃ for 4h to obtain a dehydrogenation catalyst precursor.

[0055] Step 4: Take 2g of octadecylamine polyoxyethylene ether and 4g of tetraethyl orthosilicate and dissolve them in 100mL of anhydrous ethanol to prepare a solution containing a silicon source and a surfactant. Use chemical vapor deposition to deposit the octadecylamine polyoxyethylene ether and tetraethyl orthosilicate in the solution on the surface of the dehydrogenation catalyst precursor. The specific conditions are: at 80°C, the contact time between the solution and the dehydrogenation catalyst precursor is controlled to be 5s by adjusting the flow rate of carrier gas H2, the raw materials are introduced in pulses, the deposition temperature is controlled at 280°C, and the dehydrogenation catalyst RH01 is obtained after reacting for 1h.

[0056] Example 2

[0057] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:

[0058] Step 1: Take 10g of aluminum nitride powder and put it into a high-energy ball mill, add 0.1g of aluminate and 0.06g of palm oil for surface treatment for 3h to obtain modified aluminum nitride powder.

[0059] Take 0.3g of modified aluminum nitride powder and mix it with 50g of active γ-Al2O3 powder, add an appropriate amount of hydroxypropyl methylcellulose solution, roll it into 2-4mm particles, dry it at 120℃ for 5h, and calcine it at 500℃ for 2h to obtain the alumina carrier core with enhanced heat transfer.

[0060] Step 2: Weigh 8.89 g of titanyl sulfate, 4.49 g of ammonium cerium nitrate, and 3.85 g of indium nitrate, dissolve them in 40 mL of deionized water, control the solution temperature at 55°C, quickly add 40 g of active γ-Al2O3 carrier beads, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 110°C for 7 hours, and calcine at 450°C for 3 hours to obtain carrier 2 with a defective anchoring layer.

[0061] Step 3: Weigh 3.0g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of carrier 2 with defective anchor layer, put it into an ultrasonic oscillator and oscillate it, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads, dry them at 110℃ for 8h after impregnation, and calcine them at 400℃ for 2h. Immerse the beads in 3.5wt.% sodium borohydride solution, reduce them at 30℃ for 2h, then take out the beads and dry them at 120℃ for 4h to obtain a dehydrogenation catalyst precursor.

[0062] Step 4: Take 1g of coconut oil monoethanolamide polyoxyethylene ether and 3g of hexadecyltrimethylsilane and dissolve them in 100mL of anhydrous ethanol to prepare a solution containing a silicon source and a surfactant. Use chemical vapor deposition to deposit the coconut oil monoethanolamide polyoxyethylene ether and hexadecyltrimethylsilane in the solution on the surface of the dehydrogenation catalyst precursor. The specific conditions are: place at 85°C, control the contact time to 5s by adjusting the flow rate of carrier gas H2, introduce the raw materials in pulses, control the deposition temperature at 300°C, and obtain the dehydrogenation catalyst RH02 after reacting for 2h.

[0063] Example 3

[0064] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:

[0065] Step 1: Take 10g of ultrafine zirconium oxide powder and put it into a high-energy ball mill, add 0.1g of polydopamine and 0.08g of coconut oil for surface treatment for 3h to obtain modified zirconium oxide powder.

[0066] Take 0.3g of modified zirconia powder and mix it with 50g of active γ-Al2O3 powder, add an appropriate amount of hydroxypropyl methylcellulose solution, roll and shape it into 2-4mm particles, dry it at 120℃ for 5h, and calcine it at 500℃ for 2h to obtain the alumina carrier core.

[0067] Step 2: Weigh 17.78 g of titanyl sulfate and 3.9 g of tin tetrachloride, dissolve them in 40 mL of deionized water, control the solution temperature at 50°C, quickly add 40 g of active γ-Al2O3 carrier beads, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 120°C for 5 hours, and calcine at 550°C for 2 hours to obtain carrier 3 with a defective anchoring layer.

[0068] Step 3: Weigh 3.0g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of carrier 3 with defective anchor layer, put it into an ultrasonic oscillator and oscillate it, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads, dry at 90℃ for 11h after impregnation, and calcine at 350℃ for 3h. Immerse the beads in 4wt.% ascorbic acid solution, reduce them at 40℃ for 4h, then take out the beads and dry them at 110℃ for 5h to obtain a dehydrogenation catalyst precursor.

[0069] Step 4: Take 2g of fatty alcohol polyoxypropylene ether and 4.5g of hexamethyldisilazane and dissolve them in 100mL of anhydrous ethanol to prepare a solution containing a silicon source and a surfactant. Use chemical vapor deposition to deposit the fatty alcohol polyoxypropylene ether and hexamethyldisilazane in the solution on the surface of the dehydrogenation catalyst precursor. The specific conditions are: place at 70°C, control the contact time to 5s by adjusting the flow rate of carrier gas H2, introduce the raw materials in pulses, control the deposition temperature to 300°C, and obtain the dehydrogenation catalyst RH03 after reacting for 2h.

[0070] Example 4

[0071] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:

[0072] Step 1: Take 10g of silicon carbide and put it into a high-energy ball mill, add 0.2g of aluminate and 0.06g of palm oil and treat the surface for 3.5h to obtain modified silicon carbide.

[0073] Take 0.2g of modified silicon carbide and mix it with 50g of active γ-Al2O3 powder, add an appropriate amount of hydroxypropyl methylcellulose solution, roll and shape it into 2-4mm particles, dry it at 110℃ for 6h, and calcine it at 500℃ for 2h to obtain the alumina carrier core with enhanced heat transfer.

[0074] Step 2: Weigh 1.03g of ammonium tungstate and 3.9g of tin tetrachloride, dissolve in 40mL of deionized water, control the solution temperature at 35°C, quickly add 40g of active γ-Al2O3 carrier beads, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 110°C for 7h, and calcine at 500°C for 2h to obtain carrier 4 with a defective anchoring layer.

[0075] Step 3: Weigh 3.0g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of the carrier 4 with a defective anchoring layer, put it into an ultrasonic oscillator for oscillation, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads. After impregnation, dry at 105℃ for 9h and calcine at 350℃ for 3h. Immerse the beads in 4wt.% ascorbic acid solution, reduce them at 40℃ for 4h, then take out the beads and dry them at 120℃ for 44h to obtain a dehydrogenation catalyst precursor.

[0076] Step 4: Take 2g of octadecylamine polyoxyethylene ether and 3.5g of triisopropylsilane and dissolve them in 100mL of anhydrous ethanol to prepare a solution containing a silicon source and a surfactant. Use chemical vapor deposition to deposit octadecylamine polyoxyethylene ether and triisopropylsilane in the solution on the surface of the dehydrogenation catalyst precursor. The specific conditions are: set at 85°C, control the contact time to 4s by adjusting the flow rate of carrier gas H2, introduce the raw materials in pulses, control the deposition temperature to 340°C, and obtain the dehydrogenation catalyst RH04 after reacting for 2h.

[0077] Example 5

[0078] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:

[0079] Step 1: Take 10g of boron nitride and put it into a high-energy ball mill, add 0.1g of silane coupling agent and 0.07g of palm oil for surface treatment for 3h to obtain modified boron nitride.

[0080] Take 0.3g of modified boron nitride and mix it with 50g of active γ-Al2O3 powder, add an appropriate amount of hydroxypropyl methylcellulose solution, roll and shape it into 2-4mm particles, dry it at 120℃ for 5h, and calcine it at 500℃ for 2h to obtain the alumina carrier core.

[0081] Step 2: Weigh 2.24 g of ammonium cerium nitrate and 3.85 g of indium nitrate, dissolve them in 40 mL of deionized water, control the solution temperature at 25°C, quickly add 40 g of active γ-Al2O3 carrier beads, stir evenly and leave for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 105°C for 8 hours, and calcine them at 450°C for 3 hours to obtain carrier 5 with a defective anchoring layer.

[0082] Step 3: Weigh 3.0g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of the carrier 5 with a defective anchoring layer, put it into an ultrasonic oscillator for oscillation, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads, dry at 120℃ for 5h after impregnation, and calcine at 400℃ for 2h. Immerse the beads in a 3.8wt.% sodium borohydride solution, reduce them at 30℃ for 4h, then take out the beads, and dry them at 105℃ for 6h to obtain a dehydrogenation catalyst precursor.

[0083] Step 4: Take 2.5g of octadecylamine polyoxyethylene ether and 5.0g of tetraethyl orthosilicate and dissolve them in 100mL of anhydrous ethanol to prepare a solution containing a silicon source and a surfactant. Use chemical vapor deposition to deposit octadecylamine polyoxyethylene ether and tetraethyl orthosilicate in the solution on the surface of the dehydrogenation catalyst precursor. The specific conditions are: place at 80°C, control the contact time to 6s by adjusting the flow rate of carrier gas H2, introduce the raw materials in pulses, control the deposition temperature to 350°C, and obtain the dehydrogenation catalyst RH05 after reacting for 3h.

[0084] Example 6

[0085] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:

[0086] Step 1: Take 10g of silicon nitride and put it into a high-energy ball mill, add 0.1g of silane coupling agent, 0.15g of polydopamine and 0.06g of palm oil for surface treatment for 3.5h, and dry at 105℃ for 8h to obtain modified silicon nitride powder.

[0087] Take 0.3g of modified silicon nitride and mix it with 50g of active γ-Al2O3 powder, add an appropriate amount of hydroxypropyl methylcellulose solution, roll and shape it into 2-4mm particles, dry it at 120℃ for 5h, and calcine it at 500℃ for 2h to obtain the alumina carrier core with enhanced heat transfer.

[0088] Step 2: Weigh 8.89 g of titanyl sulfate, 4.49 g of ammonium cerium nitrate, and 3.85 g of indium nitrate, dissolve them in 40 mL of deionized water, control the solution temperature at 55°C, quickly add 40 g of active γ-Al2O3 carrier beads, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 110°C for 7 hours, and calcine at 450°C for 3 hours to obtain carrier 2 with a defective anchoring layer.

[0089] Step 3: Weigh 3.0g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of carrier 2 with defective anchor layer, put it into an ultrasonic oscillator and oscillate it, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads, dry them at 110℃ for 8h after impregnation, and calcine them at 400℃ for 2h. Immerse the beads in 3.0wt.% hydrated hydrazine solution, reduce them at 30℃ for 2h, then take out the beads and dry them at 120℃ for 4h to obtain a dehydrogenation catalyst precursor.

[0090] Step 4: Take 1g of coconut oil monoethanolamide polyoxyethylene ether and 3g of hexadecyltrimethylsilane and dissolve them in 100mL of anhydrous ethanol to prepare a solution containing a silicon source and a surfactant. Use chemical vapor deposition to deposit the coconut oil monoethanolamide polyoxyethylene ether and hexadecyltrimethylsilane in the solution on the surface of the dehydrogenation catalyst precursor. The specific conditions are: place at 85°C, control the contact time to 2s by adjusting the flow rate of carrier gas H2, pulse the raw materials, control the deposition temperature at 300°C, and react for 2h to obtain the dehydrogenation catalyst RH06.

[0091] Example 7

[0092] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:

[0093] Step 1: Take 10g of silicon carbide and put it into a high-energy ball mill, add 0.1g of aluminate and 0.07g of coconut oil and treat the surface for 3h to obtain modified silicon carbide.

[0094] Take 0.3g of modified silicon carbide and mix it with 50g of active γ-Al2O3 powder, add an appropriate amount of hydroxypropyl methylcellulose solution, roll and shape it into 2-4mm particles, dry it at 120℃ for 5h, and calcine it at 500℃ for 2h to obtain the alumina carrier core.

[0095] Step 2: Weigh 17.78 g of titanyl sulfate and 3.9 g of tin tetrachloride, dissolve them in 40 mL of deionized water, control the solution temperature at 50°C, quickly add 40 g of active γ-Al2O3 carrier beads, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 120°C for 5 hours, and calcine at 550°C for 2 hours to obtain carrier 3 with a defective anchoring layer.

[0096] Step 3: Weigh 3.0g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of carrier 3 with defective anchoring layer, put it into an ultrasonic oscillator and oscillate it, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads, dry at 90℃ for 11h after impregnation, and calcine at 350℃ for 3h. Immerse the beads in 4wt.% ascorbic acid solution, reduce them at 40℃ for 4h, then take out the beads and dry them at 110℃ for 5h to obtain a dehydrogenation catalyst precursor.

[0097] Step 4: Take 2g of fatty alcohol polyoxypropylene ether and 3.5g of hexamethyldisilazane and dissolve them in 100mL of anhydrous ethanol to prepare a solution containing a silicon source and a surfactant. Use chemical vapor deposition to deposit the fatty alcohol polyoxypropylene ether and hexamethyldisilazane in the solution on the surface of the dehydrogenation catalyst precursor. The specific conditions are: place at 70°C, control the contact time to 2s by adjusting the flow rate of carrier gas H2, introduce the raw materials in pulses, control the deposition temperature to 280°C, and obtain the dehydrogenation catalyst RH07 after reacting for 2h.

[0098] Example 8

[0099] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:

[0100] Step 1: Take 10g of ultrafine zirconium oxide and put it into a high-energy ball mill, add 0.2g of aluminate and 0.06g of palm oil and treat the surface for 3.5h to obtain modified zirconium oxide.

[0101] Take 0.2g of modified ultrafine zirconia and mix it with 50g of active γ-Al2O3 powder, add appropriate amount of hydroxypropyl methylcellulose solution, roll into balls to form particles of 2-4mm, dry at 110℃ for 6h, and calcine at 500℃ for 2h to obtain the alumina carrier core with enhanced heat transfer.

[0102] Step 2: Weigh 8.89 g of titanyl sulfate, 4.49 g of ammonium cerium nitrate, and 3.85 g of indium nitrate, dissolve them in 40 mL of deionized water, control the solution temperature at 55°C, quickly add 40 g of active γ-Al2O3 carrier beads, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 110°C for 7 hours, and calcine at 450°C for 3 hours to obtain carrier 2 with a defective anchoring layer.

[0103] Step 3: Weigh 3.8g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of carrier 2 with defective anchor layer, put it into an ultrasonic oscillator and oscillate it, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads, dry them at 110℃ for 8h after impregnation, and calcine them at 400℃ for 2h. Immerse the beads in 3.5wt.% sodium borohydride solution, reduce them at 30℃ for 2h, then take out the beads and dry them at 120℃ for 4h to obtain a dehydrogenation catalyst precursor.

[0104] Step 4: Take 2.5g of octadecylamine polyoxyethylene ether and 5g of tetraethyl orthosilicate and dissolve them in 100mL of anhydrous ethanol to prepare a solution containing a silicon source and a surfactant. Use chemical vapor deposition to deposit the octadecylamine polyoxyethylene ether and tetraethyl orthosilicate in the solution on the surface of the dehydrogenation catalyst precursor. The specific conditions are: place at 85°C, control the contact time to 5s by adjusting the flow rate of carrier gas H2, introduce the raw materials in pulses, control the deposition temperature to 300°C, and obtain the dehydrogenation catalyst RH08 after reacting for 3h.

[0105] Example 9

[0106] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:

[0107] Step 1: Take 10g of ultrafine alumina powder and put it into a high-energy ball mill, add 0.1g of titanate and 0.08g of coconut oil for surface treatment for 3h to obtain modified alumina powder.

[0108] Take 0.3g of modified alumina powder and mix it with 50g of active γ-Al2O3 powder, add an appropriate amount of hydroxypropyl methylcellulose solution, roll and shape it into 2-4mm particles, dry it at 120℃ for 5h, and calcine it at 500℃ for 2h to obtain the alumina carrier core.

[0109] Step 2: Weigh 8.89 g of titanyl sulfate, 4.49 g of ammonium cerium nitrate, and 3.85 g of indium nitrate, dissolve them in 40 mL of deionized water, control the solution temperature at 55°C, quickly add 40 g of active γ-Al2O3 carrier beads, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 110°C for 7 hours, and calcine at 450°C for 3 hours to obtain carrier 2 with a defective anchoring layer.

[0110] Step 3: Weigh 3.8g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of carrier 2 with defective anchor layer, put it into an ultrasonic oscillator and oscillate it, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads, dry them at 110℃ for 8h after impregnation, and calcine them at 400℃ for 2h. Immerse the beads in 3.5wt.% sodium borohydride solution, reduce them at 30℃ for 2h, then take out the beads and dry them at 120℃ for 4h to obtain a dehydrogenation catalyst precursor.

[0111] Step 4: Take 2.5g of octadecylamine polyoxyethylene ether and 5g of tetraethyl orthosilicate and dissolve them in 100mL of anhydrous ethanol to prepare a solution containing a silicon source and a surfactant. Use chemical vapor deposition to deposit the octadecylamine polyoxyethylene ether and tetraethyl orthosilicate in the solution on the surface of the dehydrogenation catalyst precursor. The specific conditions are: place at 85°C, control the contact time to 5s by adjusting the flow rate of carrier gas H2, introduce the raw materials in pulses, control the deposition temperature to 300°C, and obtain the dehydrogenation catalyst RH09 after reacting for 3h.

[0112] Comparative Example 1

[0113] Compared with Example 2, in this comparative example 1, the catalyst preparation does not add defect anchoring oxide and protective layer SiO2 shell, and the preparation method is specifically as follows:

[0114] Step 1: Take 10g of aluminum nitride powder and put it into a high-energy ball mill, add 0.1g of aluminate and 0.06g of palm oil for surface treatment for 3h to obtain modified aluminum nitride powder.

[0115] Take 0.3g of modified aluminum nitride powder and mix it with 50g of active γ-Al2O3 powder, add an appropriate amount of hydroxypropyl methylcellulose solution, roll and shape it into 2-4mm particles, dry it at 120℃ for 5h, and calcine it at 500℃ for 2h to obtain the alumina carrier core.

[0116] Step 2: Weigh 3.0g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of active γ-Al2O3 carrier beads, put them into an ultrasonic oscillator and oscillate them at a power of 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads obtained in step 1. After impregnation, dry them at 120℃ for 8h and calcine them at 400℃ for 2h. Immerse the beads in 3.5wt.% sodium borohydride solution, reduce them at 30℃ for 2h, then take out the beads and dry them at 120℃ for 4h to obtain dehydrogenation catalyst R01.

[0117] Comparative Example 2

[0118] Compared with Example 2, the catalyst preparation in Comparative Example 2 does not add a protective layer SiO2 shell, and the preparation method is specifically as follows:

[0119] Step 1: Take 10g of aluminum nitride powder and put it into a high-energy ball mill, add 0.1g of aluminate and 0.06g of palm oil for surface treatment for 3h to obtain modified aluminum nitride powder.

[0120] Take 0.3g of modified aluminum nitride powder and mix it with 50g of active γ-Al2O3 powder, add an appropriate amount of hydroxypropyl methylcellulose solution, roll and shape it into 2-4mm particles, dry it at 120℃ for 5h, and calcine it at 500℃ for 2h to obtain the alumina carrier core.

[0121] Step 2: Weigh 8.89 g of titanyl sulfate, 4.49 g of ammonium cerium nitrate, and 3.85 g of indium nitrate, dissolve them in 40 mL of deionized water, control the solution temperature at 55°C, quickly add 40 g of active γ-Al2O3 carrier beads, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 110°C for 7 hours, and calcine at 450°C for 3 hours to obtain carrier 2 with a defective anchoring layer.

[0122] Step 3: Weigh 3.0g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of carrier 2 with defective anchor layer, put it into an ultrasonic oscillator for oscillation, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads, dry at 110℃ for 8h after impregnation, and calcine at 400℃ for 2h. Immerse the beads in 3.5wt.% sodium borohydride solution, reduce at 30℃ for 2h, then take out the beads, dry at 120℃ for 4h, and obtain dehydrogenation catalyst R02.

[0123] Comparative Example 3

[0124] Compared with Example 2, in Comparative Example 3, no high thermal conductivity material is added to the inner core of the alumina carrier, and no protective layer SiO2 shell is added. The preparation method of the catalyst in this comparative example is specifically as follows:

[0125] Step 1: Take 50g of active γ-Al2O3 powder and mix it, add an appropriate amount of hydroxypropyl methylcellulose solution, roll it into 2-4mm particles, dry it at 120℃ for 5h, and calcine it at 500℃ for 2h to obtain the alumina carrier core.

[0126] Step 2: Weigh 8.89g of titanyl sulfate, 4.49g of ammonium cerium nitrate, and 3.85g of indium nitrate, dissolve in 40mL of deionized water, control the solution temperature at 35°C, quickly add 40g of active γ-Al2O3 carrier beads, stir evenly and let stand for a while, after the bubbles on the surface of the beads disappear, take out the beads and dry them at 110°C for 6h, and calcine at 500°C for 3h to obtain a carrier with a defective anchoring layer.

[0127] Step 3: Weigh 3.0g of 10mg Pd / g palladium nitrate solution, add 9mL deionized water and mix evenly to form a precursor solution; weigh 30g of the carrier with a defective anchoring layer, put it into an ultrasonic oscillator and oscillate it, set the power to 200W, atomize the precursor solution into 10-50μm droplets and continuously spray them onto the carrier beads, dry them at 120℃ for 5h after impregnation, and calcine them at 400℃ for 2h. Immerse the beads in a 3.5wt.% sodium borohydride solution, reduce them at 30℃ for 2h, then take out the beads and dry them at 120℃ for 4h to obtain dehydrogenation catalyst R03.

[0128] Catalyst performance test

[0129] The catalysts prepared in Examples 1-9 and Comparative Examples 1-3 were respectively subjected to dehydrogenation activity and performance evaluation after hydrothermal aging in a fixed bed reactor. The catalysts did not need to be reduced and activated before testing. Each catalyst was subjected to dehydrogenation activity evaluation for 10 h. After hydrothermal aging, the dehydrogenation activity was evaluated for 10 h in an atmosphere containing 5 vol% H2O. Dehydrogenation activity evaluation conditions: catalyst loading of 15 g, space velocity of 12000 h -1 , pressure 0.2MPa, bed temperature 120℃. Raw gas composition: 1.2% H2, 0.7% O2, 0.098% CO, 0.049% CH4, 2.0% N2, remaining CO2. Hydrothermal aging conditions: N2 space velocity 2000h -1 , H2O content 10 vol%, aging at 650℃ for 10h. The evaluation results of the catalyst dehydrogenation performance are shown in Table 1.

[0130] Table 1 Test results of catalytic oxidation dehydrogenation performance of the catalyst of the present invention

[0131]

[0132] It can be seen from the above examples that the catalyst of the present invention can significantly enhance heat transfer efficiency, improve dehydrogenation accuracy, reduce the negative impact of hydrothermal aging on catalyst activity, enhance catalyst stability, and extend catalyst life.

[0133] The above description is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any person familiar with the technology can understand and think of any changes or substitutions within the technical scope disclosed by the present invention, which should be included in the scope of the present invention.

Claims

1. A heat transfer enhanced, highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst, characterized in that: The catalyst comprises, from the inside to the outside, an alumina carrier core, a defect anchoring layer, a noble metal layer and a protective outer shell layer; The alumina carrier is a particle made by mixing active γ-Al2O3 and a coated high thermal conductivity material, and the mass of the coated high thermal conductivity material is 0.1% to 3% of the mass of γ-Al2O3; The defect anchoring layer is composed of oxides that have strong interactions with metals, including WO a 、TiO b 、CeO c ,In2O3 and SnO d At least one of the following, wherein a=2-3, b=1-2, c=1.5-2, d=1-2, and the oxide content is 2.0-10.0% of the mass of the alumina carrier; The noble metal layer is composed of the noble metal element Pd, and its content is 0.05-0.15% of the mass of the alumina carrier; The protective shell layer is porous SiO2 with a thickness of 5 to 12 nm.

2. The heat transfer enhanced and highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst according to claim 1, characterized in that: The specific surface area of ​​γ-Al2O3 powder is greater than 400m 2 / g; Preferably, the coated high thermal conductivity material is a high thermal conductivity material with a coating agent coated on the surface; More preferably, the high thermal conductivity material includes at least one of ultrafine alumina powder, ultrafine zirconium oxide, aluminum nitride, boron nitride, silicon nitride, and silicon carbide; More preferably, the coating agent includes at least one of polydopamine, titanate, silane coupling agent and aluminate; More preferably, the mass of the coating agent is 0.1-3% of the mass of the high thermal conductivity material.

3. The method for preparing a heat transfer enhanced highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst according to claim 1 or 2, characterized in that: The steps include: S1. Preparation of alumina carrier core: ball milling a high thermal conductivity material, a coating agent and a liquid grease, and then adding active γ-Al2O3 powder to mix, and then adding a binder solution, rolling ball forming particles, calcining, to obtain a heat transfer enhanced alumina carrier core; S2. Preparation of defect anchoring layer: take an oxide precursor salt having a strong interaction with the metal, add water to prepare a solution, add the alumina support prepared in step S1 to the solution, stir evenly, remove the support after the surface bubbles disappear, dry, and calcine to form a support having a defect anchoring layer; S3. Preparation of a noble metal layer: Take the carrier having a defective anchoring layer obtained in step S2, impregnate the noble metal precursor solution by ultrasonic spraying, and obtain a dehydrogenation catalyst precursor by drying, calcining, and liquid phase reduction; S4. Preparation of protective shell layer: using chemical vapor deposition method to deposit a solution containing silicon source and surfactant on the surface of dehydrogenation catalyst precursor, and forming a porous SiO2 protective shell after drying and pre-decomposition.

4. The method for preparing a heat transfer enhanced highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst according to claim 3, characterized in that: In step S1, the drying time is 2 to 12 hours at 50 to 120° C. and the calcination time is 1 to 8 hours at 300 to 550° C.; The binder solution includes a hydroxypropyl methylcellulose solution with a concentration of 1 to 5 wt %; The ball forming particle size is 2 to 4 mm; The liquid oil includes oil with saturated fatty acid higher than 50%, preferably palm oil or coconut oil.

5. The method for preparing a heat transfer enhanced highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst according to claim 3 or 4, characterized in that: In step S2, the oxide precursor salt includes ammonium tungstate [(NH4)6W7O 24 At least one of: titanium oxysulfate [TiOSO4·XH2SO4·8H2O], cerium ammonium nitrate [Ce(NO3)3·6H2O], indium nitrate [In(NO3)3] and tin tetrachloride [SnCl4]; The concentration of the oxide precursor salt solution is 0.01 to 1 mol / L.

6. The method for preparing a heat transfer enhanced highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst according to claim 3 or 4, characterized in that: In step S3, the carrier with the defective anchoring layer obtained in step S2 is placed in an ultrasonic oscillator for oscillation, and the noble metal precursor solution is atomized and sprayed onto the carrier beads, and then dried, calcined, and liquid-phase reduced after the impregnation is completed; Preferably, the noble metal precursor comprises palladium nitrate and / or palladium chloride; Preferably, the concentration of the noble metal precursor solution is 5 to 10 mg Pd / g; Preferably, the drying time is 2 to 12 hours at 50 to 120°C; the calcination time is 1 to 8 hours at 300 to 550°C; Preferably, the liquid phase reduction conditions are: immersing the dried and calcined carrier in a reducing agent solution, and performing a reduction reaction at room temperature to 90° C. for 1 to 5 hours; the reducing agent includes at least one of ascorbic acid, hydrated hydrazine and sodium borohydride, and the mass concentration of the reducing agent solution is 0.5 to 6%.

7. The method for preparing a heat transfer enhanced highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst according to claim 3 or 4, characterized in that: In step S4, the silicon source includes at least one of hexadecyltrimethylsilane, polydimethylsiloxane, hexamethyldisilazane, tetraethyl orthosilicate, and triisopropylsilane, and the amount of the silicon source is such that the mass fraction of SiO2 in the final catalyst is 0.1 to 0.5%; The surfactant comprises at least one of coconut oil monoethanolamide polyoxyethylene ether, octadecylamine polyoxyethylene ether and fatty alcohol polyoxypropylene ether, and the amount of the surfactant is 1 to 10% of the mass of the aluminum oxide; The solvent is acetone or ethanol; In the solution containing the silicon source and the surfactant, the concentration of the silicon source is 5-15wt%, and the concentration of the surfactant is 10-20wt%.

8. The method for preparing a heat transfer enhanced highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst according to claim 1, characterized in that: In step S4, the time for the solution containing the silicon source and the surfactant to contact the dehydrogenation catalyst precursor is 2 to 10 seconds, the feed temperature is 50 to 90°C, and the deposition temperature is 240 to 340°C.

9. Use of a heat transfer enhanced highly stable noble metal catalytic oxidative dehydrogenation multilayer core-shell catalyst according to claim 1 or 2, characterized in that: Applicable to the dehydrogenation of mixed gas with hydrogen content less than 1.5%v and oxygen content not less than 0.75%v.

10. The use according to claim 9, characterized in that: During dehydrogenation, the reaction temperature is 120-180°C, the reaction pressure is normal pressure-10MPa, and the space velocity is 5000-30000h -1 .

Citation Information

Patent Citations

  • Dehydrogenation catalyst for feed gas containing carbon monoxide, preparation method and application method thereof

    CN101543776B

  • Catalyst for removing hydrogen from Co2 raw gas used to synthesize urea

    CN1035256A

  • Hydrophobic catalyst for hydrogen negative low-temperature catalytic combustion and preparation method of hydrophobic catalyst

    CN113908831A

  • Dehydrogenation catalyst as well as preparation method and application thereof

    CN116099545A

  • Preparation method of hydrophobic Pd-based catalyst and hydrophobic Pd-based catalyst

    CN116422363A

Cited By

  • System and process for eliminating methane pollution in tail gas of LNG (Liquefied Natural Gas) power-driven ship based on catalyst atomization

    CN120557660A

  • Palladium type carbon monoxide combustion improver and preparation method thereof

    CN120618534A